Transnational hashtag protest movements and emancipatory politics in Africa: A three country study - Matsilele, Trust; Mpofu, Shepherd; Msimanga, Mbongeni; Tshuma, Lungile (Global Media Journal - German Edition, 2022)
This study explores three of sub-Saharan Africa’s hashtag movements: Zimbabwe’s #ZimbabweanLivesMatter, Eswatini’s #EswatiniLivesMatter and Nigeria’s #EndSARS hashtags. Theoretically, we rely on the transnational alternative digital public sphere and hashtag activism to understand how social media acted as a meeting place for mobilization and building cross boundary pollination and unitary movements. This investigation relied on a combination of virtual ethnography and purposive sampling as methodological approaches. Thematic analysis was the analytical tool employed with four themes informing this investigation: democratisation and human rights, transnational solidarity, states’ response to hashtag movements and use of parody accounts as a counter hegemonic strategy. The study found that these hashtags and movements achieved a modicum of ‘success’ by forcing some of Africa’s enduring dictatorships to make piecemeal concessions of varying degrees.